Impact of Automated Prescription Drug Monitoring Program Queries on Emergency Department Opioid Prescribing - Sun, Benjamin C. (Ann Emerg Med, 2017)
OBJECTIVE: We assessed whether an automated Prescription Drug Monitoring Program (PDMP) intervention in emergency department (ED) settings was associated with reductions in opioid prescribing and quantities. METHODS: We performed a retrospective cohort study of ED visits by Medicaid beneficiaries. We assessed the staggered implementation (pre-post) of automated PDMP queries at 86 EDs in Washington State, Jan 1, 2013 to Sep 30, 2015. The outcomes included any opioid prescribed within 1 day of the index ED visit and total dispensed morphine milligram equivalents (MMEs). The exposure was the automated PDMP query intervention. We assessed effects of automated PDMP stratified by prior high-risk opioid use. We performed multiple sensitivity analyses, including restriction to pain related visits, restriction to visits with a confirmed PDMP query, and assessment of six specific opioid high risk indicators. RESULTS: The study included 1,187,237 qualifying ED visits (898,162 pre-intervention; 289,075 post-intervention). Compared to the pre-intervention period, automated PDMP queries were not significantly associated with reductions in the proportion of visits with opioid prescribing (5.8 per 1000 encounters, 95%CI: −0.11, 11.8) or the amount of prescribed MMEs (difference 2.66, 95%CI: −0.15, 5.48). There was no evidence of selective reduction in patients with prior high risk opioid use (1.2 per 1000 encounters, 95%CI: −9.5, 12.0; MMEs: 1.22, 95%CI: −3.39, 5.82). The lack of a selective reduction in high risk patients was robust to all sensitivity analyses. CONCLUSIONS: An automated PDMP query intervention was not associated with reductions in ED opioid prescribing or quantities, even in patients with prior high-risk opioid use.